Current applications and potential future role of wireless capsule technology in Crohn's disease. (November 2014) - Hall, Barry; Holleran, Grainne; McNamara, Deirdre
Abstract Background. The development of capsule technology has modified our approach to the diagnosis of gastrointestinal disease. The relatively rapid uptake of capsule endoscopy as an important clinical tool can be largely ascribed to a number of key factors, including the fact that it is a relatively easy examination to perform in an outpatient setting. It has been established as an integral part of the investigation pathway for obscure gastrointestinal bleeding and suspected small bowel Crohn's disease (CD). Current use of capsule endoscopy. Small bowel CD can be a challenging entity to diagnose. Capsule endoscopy has been shown to be both useful and safe in patients with both suspected and established small bowel CD. In suspected disease, capsule endoscopy has both a high diagnostic yield and negative predictive value. Capsule findings lead to changes in management in up to 73% of patients with established CD. However, while the technology appears capable of detecting subtle mucosal changes not readily apparent on alternate imaging modalities, the question of what actually constitutes small bowel CD as described by capsule is an issue that remains unresolved to date. Thus, capsule endoscopy is best utilised in tandem with advanced imaging and endoscopic techniques such as balloon- assisted enteroscopy. Future developments. The development of a capsule capable of viewing the colon coupled with improvements in image quality and battery life are likely to lead to the increasing uptake of this technology. In the future, 'interactive' capsules with the ability to view the entire gastrointestinal tract may be a reality.